2005
DOI: 10.1093/jurban/jti119
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Among Marginalized Women in the Outskirts of Beirut: Determinants and Association with Health Perception

Abstract: The objective of this study was to determine the prevalence of psychological distress (PD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…However, the prevalence of parental psychological distress tends to be higher in underprivileged populations. For example, a recent study by Saab, Salem, Chaaya, and Campbell (2005) assessed the prevalence of psychological distress and its determinants in 1,869 underprivileged ever‐married women aged 15–59 years in the outskirts of Beirut, Lebanon. The prevalence of psychological distress was 46.6%, but this figure was higher among women who had more children, less education, lower income, marital discord and less social support, and who were resident in a predominantly Moslem community and participated in the labour force.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prevalence of parental psychological distress tends to be higher in underprivileged populations. For example, a recent study by Saab, Salem, Chaaya, and Campbell (2005) assessed the prevalence of psychological distress and its determinants in 1,869 underprivileged ever‐married women aged 15–59 years in the outskirts of Beirut, Lebanon. The prevalence of psychological distress was 46.6%, but this figure was higher among women who had more children, less education, lower income, marital discord and less social support, and who were resident in a predominantly Moslem community and participated in the labour force.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the already discussed UHS, the sub-sample analysis pertaining to Hey el Selloum sample, showed that a large proportion of women (42%) reported mental distress- as assessed by GHQ-12. Moreover, multivariate analysis showed that mental distress was significantly associated with reported abnormal vaginal discharge, after adjusting for relevant risk factors and reported RTIs [ 23 ]. Women considered stress to be a main cause of their discharge [ 24 ] and identified mental as well as psychological health as important elements contributing to their perception of good reproductive health [ 4 ].…”
Section: Introductionmentioning
confidence: 99%